1991
DOI: 10.1016/0016-7037(91)90127-q
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of divalent metals on calcite

Abstract: The sorption of seven divalent metals (Ba, Sr, Cd, Mn, Zn, Co, and Ni) was measured on calcite over a large initial metal (Me) concentration range (lo-' to 10e4 mol/L) in constant ionic strength (I = 0. l), equilibrium CaC03(s)-CaCOs(aq) suspensions that varied in pH. At higher initial Me concentrations (10m5 to 10m4 mol/L) geochemical calculations indicated that the equilibrium solutions were saturated with discrete solid phases of the sorbates: CdCOx(s), MnCO,(s), Zn5(OH),(C0,)2(s), Co(OH),(s), and Ni(OH),(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
270
2
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 443 publications
(300 citation statements)
references
References 54 publications
19
270
2
4
Order By: Relevance
“…It then diminishes reaching a limiting value after about 18 h. The fast initial uptake is often observed and interpreted as adsorption while the slow second uptake is explained as precipitation, recrystallization, and/or diffusion into solid for the sorption. 1,6,17) After 18 h, further uptake of Cd(II) does not occur at least in a macroscopic scale. This may be due to the unavailability of exchangeable adsorption sites for Cd(II) ions, which prevents further adsorption of Cd(II).…”
Section: Uptake Of Cd(ii)mentioning
confidence: 99%
See 3 more Smart Citations
“…It then diminishes reaching a limiting value after about 18 h. The fast initial uptake is often observed and interpreted as adsorption while the slow second uptake is explained as precipitation, recrystallization, and/or diffusion into solid for the sorption. 1,6,17) After 18 h, further uptake of Cd(II) does not occur at least in a macroscopic scale. This may be due to the unavailability of exchangeable adsorption sites for Cd(II) ions, which prevents further adsorption of Cd(II).…”
Section: Uptake Of Cd(ii)mentioning
confidence: 99%
“…[1][2][3][4][5] Among the divalent metals, cadmium (Cd) has attracted the most scientific and practical interest because it is known to have a similar ionic radius to that of Ca (about 98% of that of Ca) and a high sorption affinity to calcite. 4,5) Generally accepted mechanisms involved in calcium dissolution and cadmium adsorption on calcite are explained in terms of the following equations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More and more often, low-cost materials are investigated as adsorbents (Salam et al 2011;Hegazi 2013;Mikoda et al 2017). Experimental usage of calcite for heavy metal sorption, carried out by Zachara et al (1991), showed a good sorption capacity of that mineral. Research concerning the sorption of metals from wastewater (Brady et al 1999;Ayoub and Mehaweh 2007;Merrikhpour and Jalali 2012) showed that carbonate minerals had very good sorption properties.…”
Section: Introductionmentioning
confidence: 99%